Have Primary School Teachers Built Students’ Creativity? Theoritical and Empirical Approaches - Samsudin, Asep; Sutinah, Cucun; Puspita, Ryan Dwi (KnE Social Sciences, 2025)
Teachers’ perceptions of creativity and their behavior are key points in developing student creativity. This study aims to identify teachers’ perceptions of teacher creativity and behavior in building creativity, and the correlation between the two. The method used is descriptive quantitative and correlational with online survey techniques. The participants were elementary school teachers in Indonesia who volunteered to fill out a questionnaire. consisting of two parts: the Teacher Implicit Creativity Beliefs Scale (TICBS) and the Creativity Fostering Teacher Index (CFTI). The first questionnaire was used to identify teachers’ perceptions of creativity with a Likert scale of 1-5, while the second instrument was used to identify teacher behavior in building creativity with a semantic differential scale of 1-6. Data were processed using descriptive quantitative analysis by calculating the mean and percentage of each item. The results of the study will provide an overview of teachers’ perceptions of creativity and teacher behavior index in building creativity.